Forgive me, Baba… / Mahathir Ahamad - Ahamad, Mahathir (Universiti Teknologi MARA, Kedah, 2024)
The Academy of Language Studies, Universiti Teknologi MARA (UiTM) Cawangan Kedah is thrilled to announce the release of the fourth edition of its e-magazine, The Epitome. This publication represents our steady dedication to cultivating creativity in language and literature. The primary objective of THE EPITOME is to offer a platform for writers, educators, scholars, poets, and researchers can come together to exchange their ideas, discoveries, expertise, and narratives. Our special focus revolves around an array of creative writing genres, encompassing playwriting, short stories, songs, speeches, memoirs, literary journalism, humour writing, lyric essays, innovative essays, and personal essays, with a goal to embrace diverse linguistic expressions, with content available in four languages: English, Bahasa Melayu, Mandarin, and Arabic.